2010
DOI: 10.3182/20100705-3-be-2011.00092
|View full text |Cite
|
Sign up to set email alerts
|

Model Predictive Control of a Kaibel Distillation Column

Abstract: A Kaibel distillation column separates a feed into four products with significant lower energy consumption than a conventional sequence of binary columns. Optimal operation and control of such systems is an important task in order to obtain the potential energy savings.A laboratory column has been built at NTNU, Department of Chemical Engineering. At the time of the diploma work the laboratory column has unfortunately not been available for MPC experiments.In practical operation a control structure based on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…General industrial automatic control system was shown in Figure 3, one of which was operating function block which executed orders from plan/scheduling function layers, control function blocks were composed of feedback and feedforward algorithms, the algorithm can be classic PID or MPC or other advanced control strategies [16], the reference set points and associated logic blocks were from the operation function blocks. The movement time series of operation and control were on different time scales, the current way was control function automatically fast scale and manual low-scale operation function.…”
Section: Two-layer Control Strategy (Pid+mpc) To Achieve Optimal Opermentioning
confidence: 99%
“…General industrial automatic control system was shown in Figure 3, one of which was operating function block which executed orders from plan/scheduling function layers, control function blocks were composed of feedback and feedforward algorithms, the algorithm can be classic PID or MPC or other advanced control strategies [16], the reference set points and associated logic blocks were from the operation function blocks. The movement time series of operation and control were on different time scales, the current way was control function automatically fast scale and manual low-scale operation function.…”
Section: Two-layer Control Strategy (Pid+mpc) To Achieve Optimal Opermentioning
confidence: 99%
“…The Kaibel divided-wall column (KDWC) that separates a four-component mixture with a single wall was first proposed in 1987 and attracted increasing academic interest until Skogestad et al numerically investigated the control of a Kaibel column through model-predictive control (MPC) in 2010 due to its high complexity. Obviously, larger potential benefits, including capital and operation costs, can be gained with a KDWC than with conventional direct and indirect distillation sequences. , Furthermore, KDWC is the simplest physical structure in four-component mixture separation DWCs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a pressure-compensated temperature control strategy was proposed to solve the large offset of the lower sidestream product when facing large feed disturbances in a KDWC . In addition to the traditional single-loop PID controller used in the aforementioned literature, model-predictive control (MPC) was also applied to KDWC control . Furthermore, a two-layer control structure that combines PID and MPC and fast model-predictive control (FMPC) were utilized for KDWC control .…”
Section: Introductionmentioning
confidence: 99%
“…Their study proves the real-life practicability of MPC; they did not provide an analysis of the transient behavior of DWC under desired disturbances. Kvernland, Halvorsen, and Skogestad (2010) applied MPC on the Kaibel column that separates a feed stream into four product streams using only a single column. The main objective for optimal operation was to minimize the total impurity flow.…”
Section: Introductionmentioning
confidence: 99%